Rail Human Factors 2013
DOI: 10.1201/b13827-21
|View full text |Cite
|
Sign up to set email alerts
|

Automation effects in train driving with train protection systems – assessing person- and task-related factors

Abstract: Signals passed at danger (SPADs) are amongst the most common incidents in railway operations and are largely attributed to human errors. Train protection systems have therefore been introduced to mitigate and prevent SPADs. Overrunning and slipping past stops, however, remains an issue and very little empirical research has looked into the effects of such partial automation systems thereby, especially on the train driver's cognition, behaviour and activation state. To target this issue, an attention related in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Consistent with this, we found moderate correlations between these two scales ( r = 0.54). This supports the contention of Giesemann (2013) that the complacency potential (as traditionally measured) taps attitudes about the use of technologies. However, neither of these two scales significantly correlated with hypothetical complacency behavior.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Consistent with this, we found moderate correlations between these two scales ( r = 0.54). This supports the contention of Giesemann (2013) that the complacency potential (as traditionally measured) taps attitudes about the use of technologies. However, neither of these two scales significantly correlated with hypothetical complacency behavior.…”
Section: Discussionsupporting
confidence: 70%
“…Singh et al (1993) performed an exploratory factor analysis on their scale which revealed that the items sorted into four factors which they labeled: confidence (α = 0.82), reliance (α = 0.85), trust (α = 0.89), and safety (α = 0.95). However, it seems relatively common for researchers to compute a total scale score collapsing across the four factors – in other words, the scale is often treated as unidimensional despite the notion that it consists of four factors (e.g., Prinzel et al, 2005; Merritt and Ilgen, 2008; Giesemann, 2013; Leidheiser and Pak, 2014; Mirchi et al, 2015; Pop et al, 2015; Shah and Bliss, 2017). Other researchers have examined the factors separately but have found few clear distinctions among their effects [e.g., Hitt et al, 1999; Kozon et al, 2012 (adapted scale); Verma et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The use of train protection systems may also influence driver performance. Train drivers using a PZB train protection system, the point-wise train protection system commonly employed in Germany, were found to allocate less attention to monitoring the tracks and more attention to the driver's desk than those not using the PZB system (Giesemann & Naumann, 2015). Another study found similar results for UK train drivers operating trains equipped with ETCS (Naghiyev et al, 2017).…”
Section: Train Driver Vision and Performancementioning
confidence: 75%